Synthesis of toxyloxanthone B - Giallombardoa, Daniele; Nevin, Adam C.; Lewis, William; Nawrat, Christopher C.; Kitson, Russell R.A.; Moody, Christopher J. (Elsevier, 2014)
A synthesis of the naturally occurring xanthone toxyloxanthone B is described, in which the key step is the regioselective addition of a methyl salicylate to a substituted benzyne followed by cyclization of the intermediate aryl anion to form the xanthone, the regiochemistry of the aryne addition being confirmed by X-ray crystallography. Subsequent introduction of the pyran ring by [3,3]-rearrangement and deprotection completed the synthesis